Identifikasi Senyawa Kimia Penyusun Minyak Atsiri Syzygium (Identification Of Chemical Compound From Syzygium Essential Oil) - Mariani, Yeni; Yusro, Fathul; Yanti, Hikma (Jurnal Penelitian Hasil Hutan, 2025)
Essential oils are one of the important non-timber forest products (NTFPs), produced by plants as secondary metabolites. Plants of the Myrtaceae family are well known for producing essential oils, and Syzygium is one of its prominent genera. Species from this genus, namely Syzygium polyanthum (Salam), S. myrtifolium (Pucuk Merah), and S. aqueum (Jambu Air) are common plants that are widely cultivated as ornamentals, spices, and fruit-bearing species, and they possess significant potential as sources of essential oils. This study aimed to determine (1) the yield of essential oils from the leaves of three Syzygium species, and (2) to identify the chemical components of the obtained essential oils. The leaves of the three species were distilled using steam and water distillation to extract essential oils. The oil yield was calculated, and its chemical constituents were analyzed with GC-MS. The results showed that the highest essential oil yield was obtained from S. aqueum (0.167%), followed by S. polyanthum (0.080%) and S. myrtifolium (0.061%). The essential oil of S. myrtifolium contained the greatest number of compounds (65), followed by S. aqueum (46 compounds) and S. polyanthum (18 compounds). The main constituents of S. polyanthum essential oil were caryophyllene (40.79% rel.) and humulene (17.61% rel.); S. myrtifolium oil was dominated by 3- carene (20.05% rel.) and caryophyllene (16.45% rel.); while S. aqueum oil was mainly composed of 3- carene (23.58% rel.) and caryophyllene (18.96% rel.). Caryophyllene was identified as one of the principal compounds common to all three Syzygium species.